Towards molecular photochemionics - Margherita Venturi; Vincenzo Balzani; Roberto Ballardini; Alberto Credi; M. Teresa Gandolfi (International Journal of Photoenergy)
In the last few years there has been a great interest in developing electronics at a molecular level (molecular electronics), e.g. to construct miniaturized electric circuits that would be much smaller than the corresponding micron-scale digital logic circuits fabricated on conventional solid-state semiconductor chips. An alternative possibility to the use of electron fluxes as a means for information processing (electronics) is that of using optical beams (photonics), but up until now scarce attention has been devoted to the possibility of developing photonics at the molecular level. In this paper we review some recent achievements in the design and construction of molecular-level systems that are capable of transferring, switching, collecting, storing, and elaborating light signals. The combination of molecular photonics with chemionics can lead to a wealth of molecular-level devices capable of information processing.